New methods for seed potato production: an investigation into the production and farmer uptake of mini tubers in South Africa - Sáez Fernández, Alba (SLU/Dept. of Biosystems and Technology (from 130101), 2018)
Potatoes are by far the most produced fresh vegetable crop in South Africa. Remarkably, potato sales represent more than 30% of the turnover in the Fresh Produce Markets (FPM). The potato industry in South Africa has experienced great improvements mainly due to the development of a reliable and healthy seed industry, the introduction of potato production under irrigation and of locally developed potato cultivars that are better-adapted to the South African climate. The Agricultural Research Council (ARC), founded in 1990, played an important role by introducing the potato breeding program. Furthermore, the foundation of the Potato Certification Services in 1995 brought about a sound structure for the production of clean, healthy and viable potato seeds, which are most commonly commercialised as mini-tubers or potato seeds. The use of suitable potato cultivars and certified seeds is pivotal from an IPM point of view, as it reduces the need for agrochemicals and the incidence of diseases, therefore increasing the profitability of the crop. However, the use of agrochemicals is the main strategy to combat diseases in South African agricultural systems. Inputs-intensive, as opposed to knowledge-intensive agriculture, is environmentally degrading and not always affordable. According to the literature, the reuse of late-generation seeds from one year to the next one as a result of money shortages by poverty-stricken smallholding farmers increases the occurrence of diseases. Certified mini-tubers, namely pathogen-free potato seeds that have been cultivated in sterilised medium, are currently being produced, although not commercialised, at the potato section of the department of Vegetables and Ornamental Plants of the ARC (ARC-VOP). Mini-tubers allow for the multiplication of seed for several generations before tuber-borne diseases reach dangerous levels that compromise food and economic security. The aim of the social research is to find out, through a survey carried out in a small-scale farming community of the Kwazulu-Natal province (KZN), whether the use of mini-tubers could improve the overall sustainability of smallholding agriculture. To this end, questionnaires and semi-structures interviews are conducted in a total of 30 farms and a descriptive analysis of the data is performed. Flip Steyn, potato breeder and mini-tuber producer at the Council, is already including IPM techniques such as germplasm management and sanitation, as he certifies the mini-tubers and uses developed varieties. The biological research of this work focuses on the improvement of such IPM strategy through the use of plant growth-promoting microorganisms, namely plant growth-promoting rhizobacteria (PGPR) and fungi. Seventeen different combinations of PGPR and fungi are inoculated into the substrate where potatoes are cultivated in order to compare plant performance from three different potato cultivars. Differences in plant growth rate and performance among treatments and varieties are determined by measuring leaf area and chlorophyll fluorescence through non-destructive methods. Post-harvest tests consisting of tuber size and yield measurements are also a part of the methodology, although not carried out within the timeframe of this study, in order to observe differences between treatments and varieties. The ultimate goal of this thesis research is to communicate the findings to the ARC and the Provincial Department of Agriculture of KZN (DARD-KZN) with the purpose of engaging them in future projects regarding the use of mini-tubers to empower small-scale farmers. Results indicate that differences between varieties are statistically significant, which suggests that cultivar plays a role in plant performance. However, differences between treatments are not as obvious, and drawing conclusions with the available data is difficult. Further research needs to be carried out. The incidence of pests and diseases in small-scale farming, which reported to be the major of the surveyed farmers’ challenge, can be overcome by introducing mini-tubers in their system, yet this initiative need to be accompanied with a sound project including trainings on specific topics. The low-cost methodology developed in this study has given satisfactory and reliable results.